2012
DOI: 10.3892/or.2012.1800
|View full text |Cite
|
Sign up to set email alerts
|

Expression and correlation of Bcl-2 with pathological grades in human glioma stem cells

Abstract: Abstract. The anti-apoptotic gene, B-cell lymphoma-2 (Bcl-2), has been reported to be overexpressed in gliomas and is related to tumor prognosis, suggesting a potential therapeutic target. Additionally, recent studies have demonstrated the existence of brain glioma stem cells (BGSCs) which are tumorigenic, selfrenewable and dominate the biological behavior of gliomas. Currently BGSCs are committed as a new target of glioma therapies. However, few studies have focused on the expression of Bcl-2 in BGSCs. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The Bcl-2 family proteins accelerate cell death by the mechanism of cytochrome c release and release of apoptogenic molecules from mitochondria to the cytosol and accelerate apoptotic cell death [ 111 , 112 , 113 , 114 , 115 ]. For instance, the imbalance level of pro and anti-apoptotic genes is responsible for mitochondrial dysfunction and energy depletion in CD34 + CML stem cells and ROS-low leukemia stem cells [ 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Bcl-2 family proteins accelerate cell death by the mechanism of cytochrome c release and release of apoptogenic molecules from mitochondria to the cytosol and accelerate apoptotic cell death [ 111 , 112 , 113 , 114 , 115 ]. For instance, the imbalance level of pro and anti-apoptotic genes is responsible for mitochondrial dysfunction and energy depletion in CD34 + CML stem cells and ROS-low leukemia stem cells [ 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Bcl-2 family proteins play a pivotal role in mitochondrial-mediated apoptosis [41]. The anti-apoptotic proteins prevented cytochrome c release by forming heterodimer complexes with pro-apoptotic Bcl-2 family proteins, and Bax facilitates the release of apoptogenic molecules from mitochondria to the cytosol and accelerates apoptotic cell death [42,43,44]. The Bcl-2 protein family plays an integral role in maintaining the balance between cell survival and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it inhibits the release of cytochrome c from the mitochondria and prevents the formation of the apoptosome, activation of caspases, and eventually cell death [ 60 ]. BCL-2 protein is overexpressed in GBM [ 61 ] and recurrent tumors [ 62 ]. In vitro studies have shown that the use of antisense constructs or chemical inhibitors, such as ABT-737, is capable of mitigating the antiapoptotic effects of BCL-2 and renders the cells sensitive to cytotoxic treatments ( Table 1 ) [ 18 , 63 ].…”
Section: Signals Regulating Apoptosis In Gbmmentioning
confidence: 99%